Analysis of Enterprise Resource Planning (ERP) Implementation: Institutional Work and Institutional Logics Perspectives - Apelina Teresia; B. Linggar Yekti Nugraheni (Universitas Katolik Soegijapranata Semarang, 2022)
AbstractThis study aims to analyse the role of the ERP system in supporting the management decision-making process by using institutional logics and institutional work perspectives. This study uses primary data through semi-structured interviews and applies NVivo software for coding management. It applies purposive sampling method and generate 2 key participants. Researchers used a qualitative method based on the concept of institutional logics and institutional work to analyse the suitability of the logics embedded in the ERP system with the institutional logics applied in XYZ. Identity of the company has been disguised to avoid unintended consequences. This study finds that organisation needs to synchronise its habits and culture with the system innovation, and vice versa. Moreover, this study finds that the works of actors are important in making successful ERP implementation. Organisation actors play significant roles through political, cultural, and technical works. This study contributes to current literature on how institutional works used to explain the works of actors in the implementation of innovation. Moreover, this study supports the argument about the importance of adjustment between system innovation and organisation logics during innovation implementation. AbstrakPenelitian ini bertujuan untuk menganalisis peran sistem ERP dalam mendukung proses pengambilan keputusan manajemen menggunakan logika institusional dan perspektif kerja institusional. Penelitian ini menggunakan data primer melalui wawancara semi terstruktur dan menggunakan software NVivo untuk coding management. Metode yang digunakan adalah purposive sampling dan menghasilkan 2 partisipan kunci. Peneliti menggunakan metode kualitatif berdasarkan konsep logika institusional dan kerja institusional untuk menganalisis kesesuaian logika yang tertanam dalam sistem ERP dengan logika institusional yang diterapkan di XYZ. Identitas perusahaan telah disamarkan untuk menghindari konsekuensi yang tidak diinginkan. Studi ini menemukan bahwa organisasi perlu menyelaraskan kebiasaan dan budaya mereka dengan inovasi sistem, dan sebaliknya. Selain itu, studi ini menemukan bahwa kerja aktor penting dalam membuat implementasi ERP berhasil. Aktor organisasi memainkan peran penting melalui kerja politik, budaya dan teknis. Studi ini berkontribusi pada literatur terkini tentang bagaimana kerja institusional digunakan untuk menjelaskan kerja aktor dalam implementasi inovasi. Selain itu, penelitian ini mendukung argumen tentang pentingnya penyesuaian antara inovasi sistem dan logika organisasi selama implementasi inovasi.